Life-Spans and Blow-Up Rates for a $p$-Laplacian Parabolic Equation with General Source (Journal of Partial Differential Equations, 2024)
This article investigates the blow-up results for the initial boundary valueproblem to the quasi-linear parabolic equation with $p$-Laplacian $$u_t−∇·( |∇u|^{p−2}∇u)= f(u),$$ where $p≥2$ and the function $f(u)$ satisfies $$α\int^u_0f(s)ds≤u f(u)+βu^p+γ, u>0$$ for some positive constants $α,β,γ$ with $0